N‐Radical‐Initiated Cyclization through Insertion of Sulfur Dioxide under Photoinduced Catalyst‐Free Conditions. Issue 34 (30th May 2017) - Mao, Runyu; Yuan, Zheng; Li, Yuewen; Wu, Jie
Abstract: A N ‐radical‐initiated cyclization involving the sulfonylation of unactivated alkenes through insertion of sulfur dioxide in the presence of visible light under catalyst‐free conditions is accomplished. A range of sulfonated 3, 4‐dihydro‐2 H ‐pyrroles can be generated in good yields under photoinduced sulfonylative conditions. Additionally, the corresponding 2‐(3, 4‐dihydro‐2 H ‐pyrrol‐2‐yl)methylsulfonyl‐1‐arylethanones can be easily converted to 3, 4‐dihydro‐2 H ‐1, 4‐thiazine 1, 1‐dioxides. This photoinduced transformation occurs efficiently at room temperature under catalyst‐free conditions, and various functional groups can be tolerated. A tandem radical process is involved through the iminyl radical‐mediated cyclization with the insertion of sulfur dioxide; this process shows high efficiency and good selectivity. Abstract : A N ‐radical‐initiated cyclization with the sulfonylation of unactivated alkenes through insertion of sulfur dioxide in the presence of visible light under catalyst‐free conditions is accomplished. A range of sulfonated 3, 4‐dihydro‐2 H ‐pyrroles can be generated in good yields under the photoinduced sulfonylative conditions.